Cervical cancer screening history among women diagnosed with cervical cancer in Estonia 2017–18. (5th December 2022) - Orumaa, Madleen; Innos, Kaire; Suurna, Maria; Veerus, Piret
Abstract: Background: Despite the national cervical cancer screening programme launched in 2006, Estonia has one of the highest cervical cancer incidence rates in Europe. While the overall coverage of cervical cytology is high, the factors related to cancer screening history prior to cancer diagnosis need to be studied. Methods: In this study, we aimed to examine the 10-year screening history of women diagnosed with cervical cancer in Estonia in 2017–18, using data collected from laboratory reports from 2007 to 2018. From each report, we extracted information on the date and result of cytology and on the laboratory where the sample was assessed. We analysed these data across cancer histology, the time interval between the last test result and cancer diagnosis and the laboratory type (local or regional). Results: Among 319 women with cervical cancer, 181 (56.7%) did not have any cytology reports available. Among 138 women with at least one cytology, 60% had 1–3, 24% 4–6 and 16% ≥7 tests (mean 3.7) before cancer. In 78% of women, the last test was performed less than 5 years before cancer diagnosis and 62% of these tests did not report any abnormalities. The last cytology results differed significantly between the regional and local laboratories ( P = 0.028). Conclusion: Women received the cervical cancer diagnosis in Estonia despite having several screening tests 10 years prior to the diagnosis. The proportion of cytology tests without any abnormalities less than 5 years before the diagnosis was worryingly high and needs further investigation together with the difference between laboratory types.